(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article analyzes the reforms implemented in the cultural sphere in the Kashkadarya region during the years of independence and their impact on the lifestyle and spirituality of the population. The article examines the state policy aimed at developing culture and art, the construction of new cultural institutions, the modernization of existing ones, as well as initiatives aimed at increasing youth activity in the field of art and culture, using the example of the city of Karshi. Through these, the successes and difficulties in preserving and developing cultural heritage, restoring national values, and forming mass culture in the region are covered in detail.